For T(úa) - Pérez Lasheras, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The case of a poem by Tirso de Molina, which was believed to be unpublished until its publication in 1998, when in fact it had already been printed in the seventeenth century, warns of the precautions that must be taken when editing ancient texts, since the history of the Literature is continually rewritten, and it can never be closed.